TINJAUAN YURIDIS TERHADAP PENGGUNA NARKOTIKA YANG MELAPORKAN DIRI KE BADAN NARKOTIKA NASIONAL DAN MENDAPATKAN REHABILITASI - Agum Andi Matalata (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
ABSTRACTAt first drug used only as a tool for religious rituals and in addition it is also used for treatment, the type of drug used in the beginning was the opiate or commonly known as opium or opium. However, with the development of the times, the drug used for negative things, in the world of medicine narcotic widely used, especially in the process of patient's anesthesia before surgery. Along with the times as well, someone who at first lay against narcotics turned into an addict is difficult regardless of dependence.Addicts are "self-victimizing victims", because drug addicts suffering from dependency syndrome as a result of drug abuse were done by themselves. Rehabilitation of drug addicts is a treatment process to free addicts from dependence, rehabilitation of drug addicts is also a form of social protection that integrates drug addicts into the social order so that he could no longer carry out drug abuse.Under the law number 35 of 2009 on narcotics mentioned that mandatory drug addicts undergoing rehabilitation. However, this provision was never implemented so that the National Narcotics Agency initiative to encourage the agreement of 7 (seven) state institutions concerned to give priority to the implementation of rehabilitation for drug addicts. The study was conducted through library research to obtain secondary data and field research to obtain primary data in the form of interviews on respondents and informants.